Risk factors for pterygium in the high-altitude communities - Tin, Sim Sai; Wiwanitkti, Viroj (Nepalese Journal of Ophthalmology, 2014)
No AbstractDOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11717Nepal J Ophthalmol 2014; 6(12): 244